Espaçamentos e manejo na produção de híbridos de melancia em duas épocas - Campos, Antônio Marcos Diniz (2014)
Although Brazil is the fourth watermelon (Citrullus lanatus) producing country in ranking position, its greatest challenge is the low yield average obtained (22.5 t ha-1). Such yield, places Brazil in the 38th position in the world rank, reflecting the amount of effort still needed to increase Brazilian yield efficiency. Thus, greater knowledge about the agronomic traits of new cultivars is relevant to obtain more yield efficiency. The constant search for yield increase demands for the optimization of crop practices associated to plant density, as a function of new cultivars, planting regions and market characteristics. Spacing variation can change plant development and its response to production factors. Presently, both for watermelon fruit thinning management and plant density, the recommendations are based on old varieties in greenhouses or in agreement with empirical observations of growers and technicians. Therefore, this study evaluated the effects of plant density and fruit thinning, in different plant positions, on watermelon yield and fruit quality, under dripping irrigation, in two experimental watermelon hybrids. The experiments were done at Bayer Vegetable Seeds Experimental Farm, in Uberlândia-MG, in two seasons, from April to July (Autumn-Winter) and from August to November (Winter-Spring), consisting of two watermelon experimental hybrids (X and Y); two fruit thinning management systems (A basal, or B distal), and four plant densities (3000, 4000, 5000 e 6000 plants ha-1). Fruit average weight, fruit density, brix, flesh firmness, flesh color, hollow heart and yield were evaluated. Average fruit weight was inversely proportional to the plant density up 5000 plants ha-1. Fruit size increases again, between 5000 and 6000 plants ha-1, probably due to better use of fertilizers. Therefore, greater yield was obtained with plant density of 6000 plants ha-1, with a commercial fruit size better accepted in the market (above 10 kg). Better performance was observed in all characteristics within management A (basal), season 2 (August-November), while some characteristics showed better performance in the season 1 (April-July) under the management B (distal). Thus, basal fruit thinning becomes relevant only if there is no adequate water supply and temperature for watermelon crop. Greater yield potential was observed in hybrid X, as well as greater qualitative traits potential, especially when weather conditions were more adequate for its development. Under less favorable weather conditions (season 1) hybrid X was more responsive to basal fruit thinning (management A) considering the trait average of fruit weight, with an increase of 2.5 kg per fruit and, consequently, more responsive to yield with an increase of 11.4 t ha-1.